Tellurenated Compounds: Synthesis and Application in Ion Detection and as a Catalyst - Kaswan, Poonam (Synlett, 2024)
Tellurium is now recognized as a ‘technology-critical element’ that is quickly being used in innovative applications. The chemistry of organotellurium ligands has improved rapidly during the last three decades. Because of their enhanced accessibility and the possibility that they would display significantly different properties than their sulfur counterparts, these ligands of heavier chalcogens have sparked considerable attention. The next sections will go through the various tellurium ligands and associated transition-metal complexes. Organochalcogen ligands are exceedingly flexible ligands that may react with nearly any transition metal to form a wide range of compounds, including multidentate ligands.Tellurides of various metals have lately been investigated for potential use in storage devices, solar cells, piezoelectric, medical applications, electronics, photothermal treatment, nanoplatelets, nanocrystals, catalysis, and other fields. Researchers are interested in metal chalcogenide heterostructures because of their improved charge transport and synergistic optoelectronic and catalytic properties. A sensor for various metals based on Te electrodes and a donor ligand are used to generate electrical signals and identify different metals. Due to the scarcity of tellurium, metal telluride nanocrystal heterostructures have received less attention than metal sulfide and metal selenide nanocrystal heterostructures.1 Introduction2 Tellurenated Compounds of Zwitterionic Nature3 Synthesis of Tellurenated Ligands and Complexes4 Catalytic Application and and Suzuki–Miyara Coupling5 Tellurenated Sensors for Metal-Ion Sensing5.1 Tellurium-Ion Detectors5.2 Drawbacks/Catalyst Poisoning5.3 Disadvantages5.4 Advantages and Future Prospects6 Conclusions
Keywords: tellurenated ligands and complexes; coupling reaction; metal ion detection; catalyst